Unification of de novo and acquired ibrutinib resistance in mantle cell lymphoma - Xiaohong Zhao (Nature Portfolio, 2017)
Ibrutinib has demonstrated high response rates in B-cell lymphomas but a lot of ibrutinib-treated patients relapse with resistance. This study unified TME-mediatedde novoand acquired drug resistance through B-cell receptor signalling and PI3K-AKT-mTOR axis and provides a combination therapeutic strategy against B-cell malignancies.